PERFECTLY PERFECT ADVERBS: A LEARNER CORPUS STUDY OF THE AMPLIFIER COLLOCATIONS BY GEORGIAN LEARNERS OF ENGLISH - Makhatadze, Marine (Online Journal of Humanities ETAGTSU, 2023)
This study examines how adverbs of degree tend to collocate with particular words produced by Georgian Learners of English, both from a quantitative and qualitative perspective. Various collocation measures are used to show the strength of the bond between selected amplifiers (maximizers and boosters). The research is based on the contrastive corpus analysis of native speakers’ corpus (Michigan Corpus of Upper-Level Student Papers) and Georgian learners’ corpora (compiled by me in accordance with international learner corpus research guidelines). The aims of our research are: a) To investigate whether natives and Georgian Learners of English demonstrate similar patterns of saliency and agreement in their judgments of adverb + adjective collocations; b) To reveal the difference between the syntactic patterns and lexical meaning of the adverb + adjective collocations produced in written language by Georgian learners of English and native speakers? It is hoped that in the light of the corpus-based evidence on the nature of collocations presented in this study, metalexicographers and learners will be informed about the gaps in terms of collocations acquisition and performance. Amplifier collocations might be expected to have a more explicit and prominent place in learner lexicographic research and the language teaching curriculum. Full Text (PDF)